Problem-based learning of college students as a condition of the development of environmental consciousness when passing to the sixth technological mode - Elena Anatolyevna Ashikhmina; Oksana Anatolyevna Svetlova; Mikhail Feliksovich Fridman (Вестник Майкопского государственного технологического университета)
The relevance of the research: the development of high-end manufacturing leads to an increase in the negative impact of man on the environment. So, today the issues of developing environmental consciousness in college students are relevant.The problem statement: the negative impact of a person on the environment is increasing. However, the development of the ecological consciousness of students, awareness of the consequences of environmental impact is not at the proper level that is necessary in the transition of society to the sixth technological mode.The purpose of the research is to prove that the formation of the cognitive activity of college students in the ecological aspect is a necessary condition for the development of the ecological consciousness of college students.To solve the problem, the article considers such research methods as the analysis of pedagogical literature, observation, synthesis, generalization, considers the issues of practical application of methods on the example of classes in physical and mathematical disciplines and classes in Ecology.The conclusions: The use of mechanisms for the formation of students’ ability to show initiative in problem-dialogical interaction in matters relating to environmental problems contributes to the development of students’ environmental consciousness, the growth of their responsibility for the effectiveness of their professional activities, and the impact on the ecosystem.